On the Training in the Conditions of Application of Professional Standards in the Field of Education (on the Example of Educational Psychologist) - Egorova, M.A. (Psihologiceskaâ nauka i obrazovanie (2007), 2017)
The article presents a modern approach to the design of the basic educational program for the training of a pedagogue-psychologist, the purpose and objectives of which are set by the professional standard “Pedagogue-psychologist (educational psychologist)”. The structure of the basic educational program of bachelor and master's levels is designed according to the modular principle, and the key mechanism for achieving educational results - professional competences - is networking with partner organizations (schools, kindergartens, psychological and medico-social centers). The main criteria of network partners for the training of psychologists are described. The training module is characterized as a logically completed, relatively independent part of the educational program that forms a certain competence or group of competencies. In the curriculum the module acts as an educational unit uniting theory, practice, research work and the final modular attestation of the student. The advantages of the modular structure of the educational program, coupled with the professional standard, are presented. Представлен современный подход к проектированию основной образовательной программы подготовки педагога-психолога, цель и задачи которой задает профессиональный стандарт «Педагог-психолог (психолог в сфере образования)». Структура основной образовательной программы уровней бакалавриата и магистратуры проектируется по модульному принципу, а ключевым механизмом достижения образовательных результатов – профессиональных компетенций – становится сетевое взаимодействие с партнерскими организациями (школы, детские сады, психолого-медико-социальные центры). Описаны основные критерии сетевых партнеров по подготовке педагогов-психологов. Учебный модуль характеризуется как логически завершенная, относительно самостоятельная часть образовательной программы, которая формирует определенную компетенцию или группу компетенций. В учебном плане модуль выступает в качестве образовательной единицы, объединяющей теорию, практику, научно-исследовательскую работу и итоговую аттестацию (по модулю) студента. Приведено обоснование преимуществ модульной структуры образовательной программы, сопряженной с профессиональным стандартом.